The effects of selected drugs and dietary compounds on proliferation and apoptosis in colorectal carcinoma - Kiedrowski, Miroslaw; Mroz, Andrzej (Contemporary Oncology/Współczesna Onkologia, 2014)
Like many malignancies, the development of colorectal carcinoma (CRC) can be considered as an imbalance between the compromised process of programmed cell death (apoptosis) and excessive, uncontrolled proliferation. Several mutations and epigenetic alterations are acquired during colorectal carcinogenesis. These are responsible for the cell cycle regulation, cellular sensitivity to pro- and antiapoptotic factors, cell proliferation, angiogenesis, invasiveness, as well as metastatic potential. The molecular alterations, along with their morphological expressions, have been recognised in detail, and most of the CRC cases can be attributed to either adenoma-carcinoma or serrated neoplasia pathways: in the first, the antiapoptotic features prevail; while in the second, the proliferative activity is of the utmost importance. The aim of the work is to discuss the influence of selected drugs and dietary compounds on the proliferation and apoptosis in CRC.